Synthesis and Characterization of Iridium(III) Complexes containing (ppy)2Ir-unit and Nitrogen based Donor Ligands - Sarath D. Perera (OUSL Journal)
The treatment of 4-dimethylamino pyridine (L1) with 0.5 equivalent of [Ir(ppy)2(μ-Cl)]2 afforded the neutral yellow complex [Ir(ppy)2(L1)Cl] (1) in 81% yield (ppyH = 2-phenylpyridine). When four equivalents of L1 were reacted with an equivalent of [Ir(ppy)2(μ-Cl)]2 in the presence of NH4PF6 produced the yellow salt [Ir(ppy)2(L1)2]PF6 (2) in 96% yield. Dark brown crystals of [(ppy)2ClIr]2(μ-L2) (3) with a bridging di(4-pyridyl) acetylene ligand (L2) was isolated when [Ir(ppy)2(μ-Cl)]2 was treated with one equivalent of di(4-pyridyl) acetylene. Four iridium(III) complexes (4)-(7) of the type [Ir(ppy)2(N^N)]PF6 were prepared by reacting [Ir(ppy)2(μ-Cl)]2 with an appropriate bidentate ligand (N^N) in the molar ratio of 1:2 in the presence of NH4PF6; the products were isolated in good yields (4, 87%; 5, 92%; 6, 96%; 7, 64%) as colored solids. All new complexes were characterized using a combination of IR, NMR, mass spectrometry and elemental analysis. It is important to devise synthetic routes to cyclometallated Ir(III) complexes as they have shown interesting properties in the fields of cancer research, photovoltaic cells, etc.